Measurement of talent in volleyball: 15-month follow-up of elite adolescent players - Lidor, R.; Hershko, Y.; Bilkevitz, A.; Arnon, M.; Falk, B. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The purpose of this study was two-fold: first, to examine the contribution of a battery of physical and motor tests to early phases of talent detection and early development in volleyball, and second, to differentiate between and compare the motor ability of 16-year-old starter (S) and non-starter (NS) volleyball players. Methods: Fifteen male adolescent volleyball players underwent assessment of physical and motor ability 6 times during a 15-month training program; however, not all of them took part in each testing phase. The battery was composed of 8 physical and motor tests and 2 skill tests. The physical and motor tests included 2 speed tests, an agility run, 4 explosive power tests, and an endurance test. The skill tests evaluated service accuracy at rest and following effort. Results: All participants improved their results in all but 2 tests (endurance and skill tests) across testing phases. Comparisons between the S (n=8) and NS (n=7) revealed that only one physical explosive power test (vertical jump with approach), was found to be a good indicator for distinguishing between the 2 groups of players. Conclusion: It was concluded that the volleyball battery of tests was not sensitive enough to distinguish between the ''good'' and ''very good'' players suggesting that physical and motor tests do not reflect open skill ability in volleyball.